Outcomes of esophagectomy after noncurative endoscopic resection of early esophageal cancer. (December 2019) - Dermine, Solène; Leconte, Mahaut; Leblanc, Sarah; Dousset, Bertrand; Terris, Benoit; Berger, Arthur; Berger, Anne; Rahmi, Gabriel; Lepilliez, Vincent; Plomteux, Olivier; Leclercq, Philippe; Coriat, Romain; et al.
Background: Current guidelines recommend performing esophagectomy after endoscopic resection for early esophageal cancer when the risk of lymph node metastasis or residual cancer is found to be significant and endoscopic treatment is therefore noncurative. Our aim was to assess the safety and oncological outcomes of esophagogastric resection in this specific clinical setting. Patients and methods: A retrospective review from 2012 to 2018 was performed at four tertiary referral centers. All patients had a noncurative endoscopic resection of a clinical T1 esophageal cancer, followed by esophagectomy. Outcome measures were the rates of T0N0 specimens, overall survival, disease-free and cancer-specific survival, postoperative morbidity and mortality. Results: A total of 30 patients (13 with squamous cell carcinoma and 17 with adenocarcinoma) were included. The reasons for noncurative endoscopic resection were: positive vertical margins ( n = 12), squamous cell carcinoma with muscularis mucosae or submucosal layer invasion ( n = 3 and 9), adenocarcinoma with deep submucosal invasion ( n = 11), poorly differentiated tumor ( n = 6) and lymphovascular invasion ( n = 6). Overall, 63% of the esophagi were T0N0: most residual lesions were T1a metachronous lesions, and four (13%) patients had advanced pT status ( n = 3) or lymph node metastases ( n = 2). Overall survival, disease-free survival and cancer-specific survival were 83%, 75%, and 90% respectively. A total of 43% of patients had severe postoperative complications, and postoperative mortality was 7%. Conclusion: In this cohort, esophagectomy allowed the resection of residual advanced cancer or lymph node metastases in 13% of cases, at the cost of 43% severe morbidity and 7% mortality. Therefore, the possibility of close follow up needs to be balanced with a highly morbid surgical management in these patients.